A search for heavy Higgs bosons decaying into vector bosons in same-sign two-lepton final states in pp collisions at s $$ \sqrt{s} $$ = 13 TeV with the ATLAS detector. (Tufts University. Tisch Library., 2023)
Keywords : Higgs Physics, Hadron-Hadron Scattering, Proton-Proton Scattering.; Springer Open.